Jaminan Konsumsi Rumah Tangga Petani Sagu di Desa Sungai Tohor Kabupaten Meranti, Riau - M.Rawa El Amady (Umbara, 2017)
This study addresses the culture of debt as the socio-economic security of daily consumption sustainability of rural households in Sungai Tohor Village, Meranti Riau District. The village has become the target of many development programs from various institutions which focus on peat restoration and sago cultivation. Despite the programs, however, the number of poor household during and after the programs increased; from 30 households in 2015 to 50 households in 2016. This study aims at answer the question "What institution plays role in providing the security and the sustainability of daily consumption of households in Sungai Tohor Village? This study applied qualitative method. Data were collected through, library studies, participation observation, in-depth interviews with community leaders, village officials, sago factory owners and sago labors factory  The study finds that  tauke (big-boss) play pivotal role in the security and sustainability of daily consumption in Sungai Tohor. They are willing to provide immediate cash for the villagers for mass consumption through pajak (ijon) system. This system has helped households to survive their daily consumptions, despite the fact that this system has caused many households to lose their sago plantation. Furthermore, this system also contributes to the increase number of poor households. This research concludes that rural development program that aims to improve local economic consumption and increase the capacity of local socio-economic institution should pay attention to the local socio-economic system and institution in order to formulate a locally-grounded program.  Keywords : tauke, culture of debt, subsistence consumption, pajak